Preference of common garden pest towards edible plants / Atikah Fukaihah Amir and Nur Huzeima Mohd Hussain - Amir, Atikah Fukaihah; Mohd Hussain, Nur Huzeima (Universiti Teknologi MARA, Perak, 2022)
Growing edible plants in the home gardens has proven to help improve the quality of life. However, the appearance of garden pests in the home garden may be a problem, causing loss of productivity and spreading diseases. Therefore, this paper aims to investigate the changing patterns of common garden pests among different species of edible plants in the home garden. The research was carried out approximately 8 months (June 2020 until January 2021) with 33 species of edible plants have been tested. All tested plants in the home garden were ranged at 2 to 8 months matured growth. Data sampling were carried out in two-phases, November 2020 and January 2021 when the plants were ready to harvest and the garden pest was active. The outcome of this paper was the pattern or preferences made by garden pests towards edible plants in the home garden. Recommendations are made with biological control approach with the presence of ladybirds as predatory insects to the common garden pest.